The Impact of Digital Transformation on Customer Experience: A Study of How Firms Use Digital to Enhance CX - Sehgal, Rajesh; Soni, Sandeep (Indian Journal of Information Sources and Services, 2024)
This pandemic harmed all economies, developed and developing, because the entire world was under lockdown. The corporate community is also experiencing instability as a result of this outcry. Numerous people have experienced job loss for a variety of causes. It was hard for the business organisations to continue because the market and all of the operations were reduced or stopped. Business organisations really needed to change their strategies because the ones they had been using to succeed were no longer workable. Lockdowns, social isolation, and other restrictions made it extremely difficult for businesses to provide customers a genuine sense of their goods or services. Businesses have been forced by COVID-19 to move their product and service promotion and advertising online. in order for them to build a solid clientele even after lockdown scenarios. For corporate companies, virtual buying and an awareness of online customer behaviour are becoming essential. Due to the competitive virtual marketplace, business businesses are prioritising these things, which is the genuine requirement of the current moment. Gradually, regular Internet development and expansion have made eCommerce a part of mainstream corporate operations.